Tlingit coin armour - Unknown
Cuirass body armour, fabricated from walrus hide, string and Chinese yuan coins dating 1800-1830. donated to NMAI by Dr. A. Eugene Austin (Alonzo Eugene Austin, Jr.), 1929.